2007
DOI: 10.1051/0004-6361:20066273
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the dwarf starforming galaxy associated with GRB 060218/SN 2006aj

Abstract: Context. We present high resolution VLT UVES and low resolution FORS optical spectroscopy of supernova 2006aj and its host galaxy, associated with the nearby (z = 0.03342) gamma-ray burst GRB 060218. This host galaxy is a unique case, as it is one of the few nearby GRB host galaxies known, and it is only the second time high resolution spectra have been taken of a nearby GRB host galaxy (after GRB 980425). Aims. The resolution, wavelength range and S/N of the UVES spectrum combined with low resolution FORS spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 78 publications
11
113
0
1
Order By: Relevance
“…XRF 020903 had a late lightcurve and spectrum consistent with a supernova at z = 0.25 (Soderberg et al 2005;Bersier et al 2006). More recently, the nearby (z = 0.0331, Wiersema et al 2007) and unusual burst, XRF 060218, with a very low E peak ∼ 5 keV (Campana et al 2006) showed unambiguous evidence for an associated supernova (e.g., Sollerman et al 2006;Modjaz et al 2006;Pian et al 2006). SN 2006aj associated with XRF 060218 clearly established the close link between SNe, (GRBs) and XRFs.…”
Section: Introductionmentioning
confidence: 78%
“…XRF 020903 had a late lightcurve and spectrum consistent with a supernova at z = 0.25 (Soderberg et al 2005;Bersier et al 2006). More recently, the nearby (z = 0.0331, Wiersema et al 2007) and unusual burst, XRF 060218, with a very low E peak ∼ 5 keV (Campana et al 2006) showed unambiguous evidence for an associated supernova (e.g., Sollerman et al 2006;Modjaz et al 2006;Pian et al 2006). SN 2006aj associated with XRF 060218 clearly established the close link between SNe, (GRBs) and XRFs.…”
Section: Introductionmentioning
confidence: 78%
“…The host galaxy of SN2006aj is a low luminosity, metal-poor star-forming dwarf galaxy (Ferrero et al 2006) with an irregular morphology (Wiersema et al 2007), similar to those of other GRBs associated with SNe (Modjaz et al 2006;Sollerman et al 2006).…”
Section: Grb 060218 -Sn2006ajmentioning
confidence: 96%
“…In the case of GRB 060218/SN 2006aj, using the T e method (see Wiersema et al 2007) measure the oxygen abundance of the host as 12 + log(O/H) = 7.5 but when using the PP04 calibration the host sits at 12 + log(O/H) = 8.1. Given that the moderately low PP04 abundance of the host of SN 2007bg somewhat contradicts its extremely low luminosity, it seems that the abundance has been over-estimated.…”
Section: Host Galaxiesmentioning
confidence: 99%